Determination of online reservation for hotel services - Kohila Ranjini, Annathurai (2015)
Travel agency is an intermediary between suppliers of travel industries to customers who need their services. This intermediary is now developed as an online travel agency due to the involvement of the internet. With the emergence of internet and its application, allow the travellers to access for the information search and booking of hotel easily to be done in virtual environment. The objective of study is to explore the factor for online travel agency through exploratory factor analysis, to determine the relationship among the factors and lastly, to examine which factor influence the travellers when booking hotel through online travel agency. This research used nonprobability approach with convenience sampling method. About 450 questionnaire were given in the location of the survey, however only 410 were collected from the respondents. For the data analysis, the researcher used 398 questionnaires because the remaining 12 questionnaires were discarded. Result shows that exploratory factor analysis has identified 13 factors which were suitable for online travel agency. As for the Pearson correlation result, all the variables have positive relationships and significant with each other except for special events capabilities and repurchase intention as these two variables has negative relationships but significant between each other. Furthermore, the study extends the analysis through multiple regression analysis by considering repurchase intention as a dependent variable. Result indicates four factors (accessibility, online booking features, hotel basic infrastructure and special events capabilities) were found to be significantly influence the travellers.